Identity, Distinction and Social Spaces; film culture and the challenging of modernity (KULT_online, 2014)
In this book, Anna Schober analyses alternative film cultural circles that emerged in Germany, Austria, and Yugoslavia during the 1960s. Through an examination of discourses, films, institutions, and networks as well as interviews with some of the protagonists, she focuses on these movements which (often acting on a transnational level) challenged the homogeneity of modernity in their works and discourses, but also in the way they redefined cinema as a social institution up until now. The volume offers not only a reevaluation of an often ignored aspect of film culture, but also its reinterpretation within a broader social context under different cultural and political circumstances.